ANALISIS PEMASARAN PADI DI DESA RAJA BEJAMU KECAMATAN SINABOI KABUPATEN ROKAN HILIR - Kusnanto '; Evy Maharani; Shorea Khaswarina (Program Studi Pendidikan Ekonomi Universitas Riau, 2016)
The aims of this research are: 1) To know the channels and marketing functions ofpaddy in the Raja Bejamu village Sub- district Sinaboi Rokan Hilir Regency. 2)Analyzing of the cost, margin and marketing efficiency of rice in the RajaBejamuVillage Sub-district of Sinaboi Rokan Hilir Regency. This study wasconducted by survey method and sampling as respondents were 40 samples. Dataanalysis was using snowball sampling. The results showed that the rice marketingchannel in the Raja Bejamu Village had only one of marketing channel was startingtrader farmers to collectors and wholesalers. Marketing functions of paddy in theRaja Bejamu Village was conducted by marketing agencies such as farmes, tradersand wholesalers covering exchange function, physical function and functionfacilities. At cost of farmers for consumption is Rp 36.9. At the traders marketingcosts incurred are transport cost is Rp 326.1/kg kg and costs of sacks areRp 883.8.Meanwhile, wholesalers unloading marketing spend Rp 80/kg, transportation costsis Rp 207.5/kg and other costs (meals, drinks and cigarettes) amounted Rp 25.9/kg.Meanwhile, marketing efficiency is Rp 25.21 and benefit of Marketing is Rp 736.6 aswell as part of the farmers who received 78.13%.Keywords: marketing, paddy, raja bejamu